Challenges in the EM-based design of modern telecommunication satellite antennas. Issue 4 (2nd July 2018) - Reiche, Enrico; Schneider, Michael
Abstract : Purpose: This paper aims to introduce design challenges of modern telecommunication satellite antennas. The antenna farms accommodated on a satellite are systems of high complexity. From the radio frequency (RF) point of view, the most important design issues, e.g. high power applications in space (vacuum) or typical antenna scenarios (single/multi beam antennas), and their solution are considered. Design/methodology/approach: The paper presents the application of electro-magnetic (EM) field simulation in the design and optimisation process. The design of a telecommunications satellite antenna splits into several areas, for which different types of EM field solvers are used. Findings: The use of EM field solvers enables an accurate and efficient design approach of modern geostationary telecommunications satellite antennas. Due to the use of EM field solvers, an excellent agreement between predictions and measurement results on feed as well as antenna system level is achieved. Originality/value: This paper gives an overview of state-of-the-art telecommunications satellite antenna architectures and their efficient RF design due to the use of EM field solvers. Typical high power effects and other design issues are explained. RF engineers are encouraged to work on this exciting topic to further improve the design process and to develop new satellite antenna and feed products.